1971
DOI: 10.1126/science.173.3997.645
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Circuit Mediating Escape Responses in Crayfish

Abstract: The neuronal circuit underlying rapid abdominal flexion in response to phasic tactile stimulation comprises identified afferents, interneurons of two orders, a decision unit, and several motor neurons. The circuit is organized hierarchically as a " cascade" in which electrical synapses predominate at higher levels. Behavioral habituation results from lability at chemical junctions early in the pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…However, these additional synapses are found within the neuropil of the abdominal ganglia (16,29,32,33) and not at the site identified in Fig. 1.…”
Section: Resultsmentioning
confidence: 98%
“…However, these additional synapses are found within the neuropil of the abdominal ganglia (16,29,32,33) and not at the site identified in Fig. 1.…”
Section: Resultsmentioning
confidence: 98%
“…These studies showed that one mechanism for learning and short-term memory evident in both the gill-withdrawal reflex of Aplysia and in the tail flick response of crayfish is a change in synaptic strength brought about by modulating the release of transmitter. A decrease in transmitter release is associated with short-term habituation, whereas an increase in transmitter release occurs during short-term dishabituation and sensitization (Castellucci et al, 1970;Zucker et al, 1971;Kandel, 1974, 1976) (for early reviews, see Kandel, 1976;Carew and Sahley, 1986).…”
Section: Procedural Memorymentioning
confidence: 99%
“…Several studies have shown that with repeated activation of this afferent input, homosynaptic depression occurs at the first chemical synapse in the reflex pathway, giving rise to the hypothesis that homosynaptic depression at this synapse may provide the cellular mechanism of habituation in this system (Krasne, 1969;Zucker et al, 1971;Zucker, 1972). As recently pointed out by Krasne and Teshiba (1995), all of the experiments examining homosynaptic depression in the crayfish were carried out in acute, surgically reduced preparations that did not permit descending modulatory influences from higher brain centers to be expressed.…”
Section: Habituation In the Tail-flip Response Of Crayfishmentioning
confidence: 99%